Cryptanalysis of ultralightweight mutual authentication protocol for radio frequency identification enabled Internet of Things networks - Madiha Khalid; Umar Mujahid; Muhammad Najam-ul-Islam (International Journal of Distributed Sensor Networks)
Internet of Things is one of the most important components of modern technological systems. It allows the real time synchronization and connectivity of devices with each other and with the rest of the world. The radio frequency identification system is used as node identification mechanism in the Internet of Thing networks. Since Internet of Things involve wireless channel for communication that is open for all types of malicious adversaries, therefore many security protocols have been proposed to ensure encryption over wireless channel. To reduce the overall cost of radio frequency identification enabled Internet of Thing network security, the researchers use simple bitwise logical operations such as XOR , AND , OR , and Rot and have proposed many ultralightweight mutual authentication protocols. However, almost all the previously proposed protocols were later found to be vulnerable against several attack models. Recently, a new ultralightweight mutual authentication protocol has been proposed which involves only XOR and Rotation functions in its design and claimed to be robust against all possible attack models. In this article, we have performed cryptanalysis of this recently proposed ultralightweight mutual authentication protocol and found many pitfalls and vulnerabilities in the protocol design. We have exploited weak structure of the protocol messages and proposed three attacks against the said protocol: one desynchronization and two full disclosure attacks.